Milk progresterone concentrations using enzyme immonoassay - GOYAL, RACHNA; LAKHCHAURA, B D; KUMAR, ANIL (The Indian Journal of Animal Sciences, 2013)
In a double blind study, indigenously developed enzyme immunoasssay, viz. solid phase, liquid phase and dot blot were compared to estimate progesterone levels in the milk of 18 cattle to establish their pregnancy status. Confirmatory tests revealeD that 10 animals were pregnant and 8 were non-pregnant. Dot phase EIA both quantitative, as well as visual scoring and quantitative liquid. phase EIA, correctly diagnossed all the pregnancies. Solid phase EIA proved most unreliable as it diagnosed only 7 pregnancies correctlyÂ  and 7 non-pregnancies. Progesterone levels estimated by dot blot EIA were significantly (P